Perancangan Video Edukasi Bullying Di Kalangan Pesantren - Wina Puspita Sari; Muria Putriana; Abyan Dwi Martha; M. Reza Firdaus; Nindhiya Salma Haura (CV. ULIL ALBAB CORP, 2024)
This research aims to design and develop educational videos about bullying among Islamic boarding schools using the Research and Development (R&D) method. Bullying is a serious problem that can have a negative impact on victims, especially in educational environments such as Islamic boarding schools. Therefore, effective educational efforts are needed to reduce and prevent bullying. The R&D method used in this study involves several main stages, namely needs analysis, design, development, implementation, and evaluation. The results of the study show that this educational video is effective in increasing students' awareness and understanding of bullying. This video also succeeded in inspiring positive attitude and behavior changes among students in dealing with and preventing bullying and can be applied in Islamic boarding schools to create a safer and harmonious educational environment.